Kajian ergonomi desain sepeda fixed gear (fixie) - Ali Ramadhan; Joseph Petra Sihombing (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2017)
Fixed gear bike is a derivative of bike racing because its shape resembles a racing bike used in racing but the cost to make it is affordable to many circles. Ergonomics is the science that can be associated with the use of a bicycle as a tool that is directly related to humans. By using qualitative research method, science of ergonomics can be associated with fixed gear bikes. This research is conducted by observing fixed gear bike communal events, interviews to the bicycle designers and users of fixed gear bikes as well as literature describing ergonomics of fixed gear bikes. Fixed gear bikes are used for transportation by humans. They are used for long distance trips on the streets by the community in accordance with the form and the components of the fixed gear bikes; without of brake components, biking could endanger the user when driving it. Ergonomics is needed for fixed gear bikes because these bikes have a personal dimensions in accordance with they users. It is because fixed gear bikes are based on user needs.Keywords: bikes, fixed gear, ergonomics